A countering of the asymmetrical interpretation of the doctrine of counter-intervention. (2nd January 2021) - Henderson, Christian
ABSTRACT: Adherents to the so-called 'negative equality' principle agree that an exception exists in the form of the doctrine of counter-intervention. This exception is, however, seen as operating asymmetrically, in that while states are permitted to counter-intervene in support of governmental regimes they are not permitted to intervene in support of non-state opposition groups should the governmental regime be in receipt of prior assistance in the context of the civil war. The purpose of this article is to probe the asymmetrical interpretation of the doctrine of counter-intervention in testing whether it can be said to stand up to scrutiny, as well as explore the possibilities for a symmetrical interpretation of the doctrine and the legal and policy issues involved in extending it in this way.